ANALISIS FAKTOR-FAKTOR PEMICU PERILAKU AGRESIF ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK PERTIWI KOTA PEKANBARU - Stevi Marsel; Daviq Chairilsyah; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the observations that have been done in TK Pertiwi Pekanbaru City, the researcher found that there are some factors that cause aggressive behavior of children which always cry and revolt when they are in the class. The aggresive behaviours emerge because they force their parents to accom pany them along the learning force process. That behaviours can give bad effects to another children that tend to imitated what they look and listen. The im of this research is to find out some factors which cause the agressive behaviours of children aged 5-6 years old in TK Pertiwi Pekanbaru City. This research is done in TK Pertiwi Pekanbaru City in May-June 2016. Descriptive is a kind of this research. The populations in this research are the parents of student in TK Pertiwi Pekanbaru City they are 45 participants. The sample is part of the number and characteristics possessed by this population, when the subject is less than a hundred people is better to take them all. In this research the data collection techniques used a questionnaire (questionnaire). Based on the assessment criteria defined it can be concluded that the factors that cause aggressive behavior of children aged 5-6 years in TK Pertiwi Pekanbaru is high, because being on a percentage between 56% - 75% said